An investigation of somatosensory profiles in work related upper limb disorders: a case-control observational study protocol - Moloney, N.; Hall, Toby; Doody, C. (Biomed Central Ltd, 2010)
Background: Work related upper limb disorders constitute 45% of all occupational diseases and are a significant public health problem. A subgroup, non specific arm pain (NSAP), remains elusive in terms of understanding its pathophysiological mechanisms with its diagnosis based on the absence of specific clinical findings. One commonly proposed theory is that a neural tissue disorder is the primary dysfunction in NSAP and findings from previous studies lend some support to this theory. However, it is not clear if changes identified are simply a consequence of ongoing pain rather than due to specific neural changes. The presence of neuropathic pain has been investigated in several other musculoskeletal conditions but currently, there is no specific diagnostic tool or gold standard which permits an unequivocal diagnosis of neuropathic pain. The purpose of this study is to further describe the somatosensory profiles in patients with NSAP and to compare these profiles to a group of patients with MRI confirmed cervical radiculopathy who have been previously classified as having neuropathic pain.Methods/Design: Three groups of participants will be investigated: Groups 1 and 2 will be office workers with either NSAP or cervical radiculopathy and Group 3 will be a control group of non office workers without upper limb pain. Participants will undergo a clinical assessment, pain questionnaires (LANSS, Short Form McGill, DASH and TSK) and quantitative sensory testing comprising thermal detection and pain thresholds, vibration thresholds and pressure pain thresholds. Discussion: The spectrum of clinically suspected neuropathic pain ranges from more obvious conditions such as trigeminal neuralgia to those with vague signs of nerve disorder such as NSAP. A thorough description of the somatosensory profiles of NSAP patients and a comparison with a more defined group of patients with evidence of neuropathic pain will help in the understanding of underlying neurophysiology in NSAP and may influence future classification and intervention studies relating to this condition.